The Innovative Physics Learning Model to Improve Creative Thinking Skills: a Systematic Literature Review - Widiarini, Putu; Suma, Ketut Suma; Rapi, Ni Ketut; Suastra, I Wayan (Reflection Journal, 2025)
The aims of this paper is to describe an innovative physics learning model in developing creative thinking skills. The studies carried out were 1) indicators of creative thinking skills, 2) ways to develop creative thinking skills. This study is a Systematic Literature Review which is carried out by identifying, reviewing, evaluating and interpreting all research that has been carried out and written in the form of scientific articles. The design used is to summarize and review 20 articles that have a specific focus on research objects in journals indexed by Scopus. The results of the study state that 1) the indicators of creative thinking skills that are widely used in research are Guilford and Torrance's creative thinking; 2) there are various innovative physics learning models that can be implemented to develop creative thinking skills, including project-based learning models, STEM-based learning models, problem-based learning models, flipped classrooms, and technology-assisted learning models.